THE IMPLEMENTATION OF RELIGIOUS PLURALISM VALUES OF ISLAMIC LAW ON ARTICLE 156A OF THE CRIMINAL CODE - Rossa Ilma Silfiah (Yustisia Jurnal Hukum, 2020)
Religious freedom in Indonesia is based on the abundant presence of Godliness that is the religious values embraced in Indonesia. The religions are Islam, Christianity, Catholicism, Hinduism, Buddhism and Confucianism mentioned in the Presidential Decree No. 1 of 1965 on the defamation/blasphemy, and stipulation of Article 156a to become a part of Article 156 Criminal Code. The essence of the blasphemy law is to realize a harmonious religious life. This is in line with the Islamic law that is universal and dynamic. Islam does not deny the diversity of the universe, diversity of knowledge, diversity of tribes and cultures, and diversity of religions and beliefs. Because the messenger of the Prophet was to improve the morality of his followers by carrying the value of Rahmatan lil-aalamiin (a blessing for the universe). In this study, the values of Islamic law implicit in Article 156a of the Criminal Code were examined by applying a normative method as well as religious text approach as a framework for argumentation. In addition to applying a policy-oriented approach, this research also applied a value-oriented approach. Because the position of Islamic law is one source of material law as well as very relevant to the pluralistic style of Indonesian society.